LOCAL CONTROL OF LARGE BRAIN METASTASIS AFTER GAMMA KNIFE RADIOSURGERY IN PATIENTS WITH NON-SMALL CELL LUNG CANCER (Vietnam Journal of Community Medicine, 2026)
Objectives: Large brain metastases are defined as tumors with a diameter ≥ 3 cm or a volume ≥ 10 cm3. Large brain metastases are known to be a poor prognostic factor, and there is currently no optimal treatment. Many studies of staged radiosurgery for large brain metastases have shown high local control rates. The study aimed to evaluate the results of local control of large brain metastases in patients with non-small cell lung cancer using Gamma Knife radiosurgery.Methods: We analyzed 97 patients with non-small cell lung with large brain metastases from July 2019 to November 2025. Selected patients have brain metastases from 1 to 3 tumors, including lesions with the largest diameter > 3cm (or volume ≥ 10 cm3), KPS score ≥ 60. Patients were treated by stereotactic radiosurgery using Leksell Gamma Knife ICON unit (Elekta AB). Large brain metastases were radiosurgery with a dose of 12 Gy x 2 fractions. The remaining tumors were dosed based on the RTOG 9005. Patients were assessed for clinical symptoms and imaging response according to RANO criteria at 6 months intervals.Results: In our study, the volume of large brain metastases decreased significantly between the two fractions (p < 0.005). The local control rate of large brain metastases at 6 months was 91.8%.Conclusion: Staged Gamma Knife radiosurgery has shown promising local control for large brain metastases in patients with non-small cell lung cancer.
Keywords: radiosurgery, large brain metastases, lung cancer, local control.